Performance Analysis of Nanotube Junctionless Accumulation Mode MOSFETs with Ion Implanted Doping Profile - Baral K.; Singh P.K.; Kumar S.; Chander S.; Singh K.; Jit S. (My University, 2025)
Thispaper demonstrates the electrical characteristics such as surface potential, electric field, drain current, subthreshold swing, and thethreshold voltage of nanotube junctionless accumulation-mode MOSFETs(NJAM-M OSFETs) with ion implanted doping profile in the channel region. The ion implantation, subsequent annihilation and heat treatment of the device cause a Gaussian type doping profile. Thus, an ion implanted doping profile can be well approximated as a Gaussian doping profile. In this work, different electrical characteristics of NJAM-FETs with Gaussian type channel doping are analyzed for different straggle lengths. From the analyzed results.itcan be observed that Gaussian doping with least straggle length gives thebest performance in terms of I ON /I OFF and short channel effects. The channel length of 40nm and inside/outside radius of 3nm/ 8nm has been considered for the simulated NJAM-MOSFET. All simulation results have been obtained using VisualTCAD from COGENDA. © 2018 IEEE.